Optimizing Paste Formulation for Improving the Performances of CMOS-Based MOx Chemiresistors Prepared by Ink-Jet Printing - Claudio Zuliani; Lisa Jerg; Alison Hart; Wolfram Simmendinger; Malick Camara; Zeeshan Ali (Proceedings, 2018)
CMOS-based devices and the control of the materials properties by nanotechnology enabled significant progresses in the field of metal chemiresistors for gas sensing applications both in terms of miniaturization and performances (e.g., gas sensitivity). In this regard, ink-jet printing is a powerful technique to achieve high-volume production and meet the emerging consumer market demands. The paste formulation is an obvious aspect to consider for achieving a viscosity range suitable for ink-jet printing. More importantly, it is often an underestimated task which impacts the gas response of the resulting chemiresistors in terms of sensitivity, cross-sensitivity and baseline drift. In this manuscript, the effects on the film morphology and gas response upon removing ethyl-cellulose from the paste formulation is reported. Improvements in terms of sensitivity and baseline drift were observed.